The question of the so-called de-facto stateless persons and their protection - Balboni, Marco; Korcari, Barbara (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
The article focuses on the international concept of statelessness, which is still not universally shared. While there is no doubt that it includes the so-called de jure statelessness, a debate is still ongoing as to whether the international concept of statelessness can also include the so-called de facto statelessness. This notion refers to the condition of who, despite formally possessing a nationality or having a well-founded expectation of possessing it, is in fact - for different reasons - in a condition similar to that of the so-called de jure stateless.After briefly reconstructing the international codification on statelessness, the article explores the debate that has taken place at international level on the issue. First, it discusses the codification of the two specific conventions adopted on statelessness. Second, it analyses the subsequent debate, with the aim of reaching some conclusions. The authors argue that the notion of de facto statelessness deserves to be maintained in order to design a category of people who, due to their specific condition, may be entitled to benefit from both the protection regime provided for de jure stateless persons and the rights associated with nationality, in particular in light of the guarantees provided by international human rights law. The resulting protection will, probably, be based on an individual choice dependent on a personal assessment of one’s own situation, taking into account the circumstances of the specific case. The problem, if anything, is to strengthen the international mechanisms of protection, particularly weak in matter of statelessness.
Keywords: Statelessness; de jure Statelessness; de facto Statelessness; Human Rights Law; ineffective citizenship